Kinematic changes during learning the longswing on high bar - Williams, G.; Irwin, G.; Kerwin, D. G.; Newell, K. M. (Sports Biomechanics, 2012)
The purpose of this study is to provide evidence of technique changes during learning a sports-specific skill, the looped bar longswing (LLS). Thirteen male participants with no previous high bar experience took part in a training study. Kinematic data were collected using a CODA motion analysis system (200 Hz) during eight weekly testing sessions. Analyses focused on the amplitude of swing and the functional phase (FP) actions, defined by the rapid flexion to extension of the shoulders and extension to flexion of the hips as the performer passed through the lower vertical. Three groups were identified based on the number of sessions it took each participant to perform the LLS (G1: most successful, G2: intermediate, and G3: least successful). All participants were able to significantly increase swing amplitude over the training period (p < 0.05). For each participant the hip FP started significantly: later for G1, earlier for G2, and did not change for G3. Extension actions at the shoulders were dissimilar to those reported for elite gymnasts performing the longswing. The FP of the hips provides a mechanism to distinguish between the learners of different skill levels. The study has provided support for a single-subject design when investigating technique changes during learning.